Profiling prosecuted wildlife crimes in Kenya - Riungu, Jim; Sosnowski, Monique; Petrossian, Gohar A. (Frontiers in Conservation Science, 2025)
IntroductionThis study profiles and analyses 1,099 wildlife crime prosecutions in Kenya to understand the prevalence of crimes, species involved, arrest patterns, prosecution and sentencing outcomes.MethodsA descriptive and temporal analysis of the data is conducted to understand trends.ResultsFindings indicate that illegal grazing offenses were the most prevalent offenses followed by trophy and bushmeat related offenses. The elephant was the species most impacted by wildlife crime. Temporal results show that wildlife crimes such as poaching, illegal grazing and extraction offences peak during dry seasons and decrease in wet seasons. Most prosecutions involved single offenders and 90% of offences brought against them returned a guilty verdict. The penalty of imprisonment or payment of a fine was the most common sentence with an average imprisonment and fine for endangered species being 4 years 11 months or 340$ and 1 year 3 months and 126$ for non-endangered species respectively. We also found evidence of crime convergence with offenders engaging in other serious crime or more than one species.DiscussionIllegal grazing offences surpassed other offences reflecting broader land use challenges between pastoralism and conservation. The temporal variations reflect the need for adaptative enforcement to address the human – wildlife competition during dry seasons. Crime convergence together with predominance of single offender prosecutions suggests that law enforcement may disproportionately target low level players while larger and organized players remain underrepresented in prosecution outcomes. While harsher penalties for crimes involving endangered species compared to lesser penalties for non-endangered species is aligned with theprinciples of proportionality, the overall low level of fines raises questions about their deterrence given the high economic value driving wildlife crime. Strengthening the law enforcement response requires a livelihood sensitive approach, strong deterrence and sentencing that matches the harm caused by wildlife crimes.